Horizontal Inequalities: A Neglected Dimension of Development. - Stewart, F (CRISE (Department of International Development, University of Oxford), 2003)
Current thinking about development places individuals firmly at the centre of concern for analysis and policy. This paper explores why groups are important for individual welfare and social stability, and argues that horizontal inequalities (i.e. inequalities between culturally formed groups) is a very important but neglected dimension of development. Most attention is focussed on inequality between individuals. The paper recognises that groups are socially constructed and malleable, often with fluid membership. Nonetheless, group’s relative performance in economic, social and political dimensions is an important source of individual welfare and can cause serious political instability. This is illustrated by nine case studies, in which horizontal inequalities have led to a range of political disturbances, in some cases modified by state action to correct the inequalities. The paper concludes by pointing to an array of actions that can be taken to correct horizontal inequalities, arguing that such policies should form an important part of development strategy, but currently do not in either economic or political conditionality.